The Efficiency Of Village Funds On Community Empowerment And Village Development In Kutamakmur District, North Aceh Regency - Siti Hajar Sari; Cut Putri Melita Sari (Journal of Malikussaleh Public Economics, 2020)
This study aimed to determine the Efficiency of Village Funds for Community Empowerment and Village Development in Kuta Makmur Sub-district, North Aceh Regency. The research use secondary data in the form of the 2018 Budget Realization Reports obtained from the Kuta Makmur Sub-district office, North Aceh Regency. The data analysis technique is conducted by calculating the efficiency of village funds using the DEA method (Data Envelopment Analysis) approach to see the level of output-oriented efficiency. The results of the study showed that. In 2018, there are only 5 villages fullfil the efficient criteria. These results indicated that the realization of the village funds budget does not reach the efficient criteria and the use of village funds for Community empowerment and Village Development not optimized.Keywords: Efficiency, Village Funds, Community Empowerment, Village Development